Disempowerment, democratization and the quest for an inclusive politics in Africa - Ujomu, Philip Ogo (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2019)
The article looks for a way of establishing an endogenous humanistic and inclusive democratic order. How can we make democracy more attuned to human dignity and well-being so as to surmount the obstacles of inequity, marginality and institutional dysfunction that plagues the nation state presently? How do manage the flux created by material poverty, economic dependency, high rate of citizen illiteracy, weak political culture, social disorder and instability as well as the stricture of dualistic foreign ideological (communist versus capitalist) control on African democratic experience? The work focuses on the study of those democratic principles that include joint actions, the abandonment of monopoly or domination and the creation of a humane system of values and ways of its representation. The author objects to the existing system in African countries, which does not allow the political power to be accountable for the common good, hinders citizens’ access to broader opportunities and social amenities, as well as access to mechanisms for redress and justice. The author believes that foreign strategies impose top-down social engineering and the problem of marginalization. Key words: inclusive politics, democratic values, marginality, African countries, social justice.